Effect of herbicide and handweeding on current and subsequent season Striga hermonthica density on sorghum - Carsky, R.J.; Singh, L.; Ndikawa, R. (Informa UK Limited, 1994)
Striga hermonthica is an important cause of yield loss in sorghum in the semi‐arid zone of Africa. Two trials were conducted in northern Cameroon to evaluate the effect of herbicides for two cropping seasons on densities of emerged Striga in treatment years and on densities of Striga seed and plants in subsequent years. Herbicide application using 2,4‐D, triclopyr, paraquat, and bromoxynil and urea solution (20%) was compared with hand‐weeding of Striga and an unweeded control. Reduction of emerged Striga density was greatest with 2,4‐D and triclopyr. Sorghum grain yield was greatest in the urea solution treatment. Subsequent (third‐year) Striga seed densities were not significantly different, although they were substantially lower in the 2,4‐D‐treated plots. Emerged Striga densities in subsequent years were generally not significantly affected by previous herbicide treatments. One major source of variation in Striga density in the first year following the Striga suppression treatments was plot position along the slope, reinforcing the hypothesis that soil moisture plays a major role in Striga germination.